Moderating Role Of Psychological Resilience On Project Manager Abusive Supervision In Construction Projects In Pakistan - Rafique, Muhammad (2023)
Research acknowledged the fact that abusive supervision is a universal workplace meance and is not confined to specific organization, industry or nation. However, its empirical investigation is rare in the project management literature. Despite the fact that more recently, studies showed that majority of psychological problms employees faced in the construction projects is due to abusive behavior of the supervisors. Therefore, drawing on affective event theory (AET), the current study objective was to investigate the antecedents of project manager abusive supervision. As such, this study examine the relationship between stressors (role overload, role conflict, role ambiguity, time pressure, and work family conflict) and abusive supervision. Additionally, the study examined the mediating role of emotional exhaustion and anger between stressors and abusive supervision. The study also included the role of psychological resilience as a boundary condition between stressors and emotional exhaustion and anger. In this study, a time-lagged design with purposive sampling were utilized to collect data from 241 supervisor-subordinate dyads in the construction projects of Pakistan. Structural equation modeling were used to analyze the data. The findings revealed that stressors (role overload, role conflict, role ambiguity, time pressure and work family conflict) positively and significantly predict project manager abusive supervision. Moreover, the results suggested that both emotional exhaustion and anger significantly mediated the relationships between stressors and project manager abusive supervision.